Dietary supplementation of sodium bicarbonate, probiotic and L-ascorbic acid affects laying performance and eggshell quality in older hens - Dey, B; Ray , BC; Saha, DJ (Bangladesh Journal of Animal Science, 2022)
Eggshell quality issues are a substantial hidden cost for egg producers and a matter of concern for older hens. To address the issue, a trial was conducted to determine the effects of various dietary supplements on eggshell quality in older hens. A total of 48 Hy-line brown commercial laying hens aged 76 weeks were considered for the experiment. There were four dietary treatments with three replications per treatment, maintaining four birds per replication. All the diets had similar energy and protein contents except for the doses of test ingredients. The diets contained T1 (control: layer mash feed), T2 (control + 3g NaHCO3/kg feed), T3 (control + 2 g/kg multi-strain probiotics) and T4 (control + 0.4 g/kg L-ascorbic acid). Laying performances and eggshell qualities were measured three times during the whole experimental period. Dietary inclusions of all the test materials reflected a significant increase in egg production (p<0.0001). Similar to egg production, a rise in egg mass output (p=0.0006) was depicted in all the treated groups. An improvement (p=0.0001) in feed conversion ratio (feed:egg mass) was obtained due to the feeding of the additives as well. The addition of NaHCO3, a multi-strain probiotic, and L-ascorbic acid to the diet increased shell percent (p=0.0611) and shell thickness (p=0.0293). The inclusion of three test ingredients in the layer diet showed the better shell thickness (p=0.0293) than the control group. Taken together, it may, therefore, be opined that the dietary supplementation of sodium bicarbonate, multi-strain probiotics, and L-ascorbic acid significantly improves the quality of eggshell and overall laying performance of older hens. Bang. J. Anim. Sci. 2021. 50 (2): 92-98